Diseño de distribución en planta y optimización de los procesos productivos en la empresa “Lácteos Sotaquirá” en el municipio de Sotaquirá - Boyacá (2020)
The present work is divided into 5 stages in which various guidelines and various information surveys were generated, starting from the phase of establishing theories and concepts on which it is based, going through the diagnostic phase in which it was determined the current state of the company and the gathering and taking of important information for the development of the investigation; Diagrams and flow charts of vital importance were developed to establish the current state of the processes of the dairy lacteos Sotaquirá, also, the development of the distribution proposal allowed to establish the production times, the space required for the development of activities together with the link method which allows to establish the relationship between areas, for this reason through the development of the calculation of surfaces the proposal was developed since with this the calculation of the area necessary for the development of this method is determined, a proposal of a new product which is double cream cheese for which grass course and grass flow is ruled, a distribution proposal is made in which the company's processes are shown, finally the obtaining of the financial proposal determines the viability of the project with the information provided by the company, in which a cost-benefit analysis is carried out yielding positive results.